Answer:
1.18
Explanation:
Given the Magnitude of an earth quake model :
M = log(x/c)
x = measured amplitude ; c = reference amplitude
Amplitude of seismic wave in first earthquake = 15 amplitude of seismic wave in second
Let amplitude of seismic wave in first earthquake = x1
amplitude of seismic wave in second earthquake = x2
x1 = 15 * x2 = 15x2
Hence ;
1st earthquake magnitude :
M1 = log(a/c)
2nd earthquake magnitude :
M2 = log(15a/c)
M1 - M2
Log(x1/c) - log(x2/c)
Using the quotient rule
Log(x1) - log(c) - [log(x2) - log(c)]
Log(x1) - log(c) - log(x2) + log(c)
Log(x1) - log(x2)
Substituting x1 = 15x2
Log(x1) = log(15x2)
Seperating using product rule:
Log(x1) = log(15*x2) = log(15) + log(x2)
Hence,
log(15) + log(x2) - log(x2)
Log(15) - 0
= 1.1760
= 1.18 (nearest hundredth)